Penerapan Teknologi Non-Fungible Token (NFT) Dalam Mewujudkan Kenangan Sekolah Melalui Erinnerungennft - Roja Mei Ningsih (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
This research aims to analyze the application of Non-Fungible Token Technology (NFT) in capturing school memories through ErinnerungenNFT. The NFT phenomenon has opened up new opportunities in representing unique and non-interchangeable digital ownership, which is now used in various contexts, including in remembering school days. The research method used is a qualitative approach by combining data collection techniques through literature study and direct observation on the ErinnerungenNFT platform. The results of this research show that the application of NFT Technology on ErinnerungenNFT has the potential to be a creative means of capturing memories of school days. The utilities provide to the owner of the NFT make the owner able to re-experience the memories of school days.